The Role of the Curator as a Mediator in the Settlement of a Bankruptcy Case - I Made Arjaya; Ni Wayan Umi Martina (Sociological Jurisprudence Journal, 2019)
The purpose of this study is to look for the efforts that can be made by debtors to have their cases of bankruptcy resolved peacefully and to examine the procedures to be undertaken by Curator to achieve peace in the efforts of settling the case of so bankruptcy. This type of research is normative legal research done with a statute approach, conceptual approach, and case approach to legislation. The legal materials were collected by applying the method of library research. The results of data analysis show that in order to achieve peace in the settlement of the cases of bankruptcy, a a debtor needs to immediately make a rational peace plan that is acceptable to the creditors. In achieving this, the curator takes a key role to convice the debtors to make a good decision in preparing a plan of peace. The implication is the prepapred peace plan should be made sure capable of assuring the creditors to take. Thus, it is the curator’s responsibility to also convince the creditor to accept the plan of peace made by the bankrupt creditors. Keywords: Bankruptcy; Curator